1999
DOI: 10.1038/6683
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The crystal structure of the cytotoxic endonuclease domain from the bacterial toxin colicin E9 in complex with its cognate immunity protein Im9 reveals that the inhibitor does not bind at the active site, the core of which comprises the HNH motif found in intron-encoded homing endonucleases, but rather at an adjacent position leaving the active site exposed yet unable to bind DNA because of steric and electrostatic clashes with incoming substrate. Although its mode of action is unorthodox, Im9 is a remarkably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
108
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 65 publications
6
108
0
Order By: Relevance
“…From these studies it was argued that inactivation of the colicin occurs through steric and electrostatic occlusion of substrate DNA, consistent with solution data demonstrating the inability of the complex to bind dsDNA, even though the active site cleft of the DNase is wide enough to accommodate substrate (17). The two structures also revealed that colicin DNases are metalloproteins, containing single, tetrahedrally coordinated transition metals within their active sites, located more than 10 Å away from the proteinprotein interface.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…From these studies it was argued that inactivation of the colicin occurs through steric and electrostatic occlusion of substrate DNA, consistent with solution data demonstrating the inability of the complex to bind dsDNA, even though the active site cleft of the DNase is wide enough to accommodate substrate (17). The two structures also revealed that colicin DNases are metalloproteins, containing single, tetrahedrally coordinated transition metals within their active sites, located more than 10 Å away from the proteinprotein interface.…”
supporting
confidence: 52%
“…Thus, the immunity protein takes the form of a membrane protein that prevents the insertion of an incoming colicin into the inner membrane (16). By contrast, nuclease colicins can kill cells the moment their synthesis is complete and so have evolved a highly efficient immunity system to combat suicide (17,18). The 9.5-kDa immunity protein Im9, 1 for example, folds into its distorted fourhelical bundle structure with a rate constant of 2200 s Ϫ1 ; thus, folded immunity protein appears in Ͻ1 ms once SOS induction of the colicin operon is activated (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The immunity protein serves to protect the producing cell from the lethal effects of the toxin but must be jettisoned before translocation into the target cell. Unusually for an enzymeinhibitor complex, the immunity protein does not bind directly to the active site of the E9 DNase, but rather to an adjacent exosite (14,15). The catalytic center of the E9 DNase domain contains the HNH motif, which is the site for both DNA and metal binding (16).…”
mentioning
confidence: 99%